Possible role of tidal and rotational forcing on bradyseismic crises and volcanic unrest in the Campi Flegrei and Somma-Vesuvius areas - Lambert, S.; Sottili, G. (Frontiers in Earth Science, 2023)
Volcanic unrest at large calderas, led by the complex interaction between the degassing of the shallow magma reservoir and the overlying hydrothermal system, occurs at intervals of 10-100 years. Even if only a minority of bradyseismic crises ends with an eruption, discriminating between pre-eruptive and non-eruptive signals is fundamental for defining levels of alert. Our study explores the possible link between recent episodes of major unrest at the Campi Flegrei caldera, located in the densely inhabited area near the city of Naples (Italy), and the astronomical forcing arising from both lunisolar tides and Earth's rotation. We analyze seismic data at Mount Vesuvius and Campi Flegrei sites and find significant correlation between the multiyear variation of the seismic energy and the tidal part of the strain, whereas the correlation with the rotational part from polar motion and length-of-day variations is more elusive. The near-zero time-lag between strain and seismicity suggests a rapid response of the seismicity to the excitation. We discuss how our findings are line with previous works evidencing how the decompression of the low-viscosity, mafic magma reservoir results in a rapid release of dissolved volatiles which in turn produces an abrupt acceleration in the Campi Flegrei caldera geochemical and geophysical signals.